The impact of loneliness and social adaptation on depressive symptoms: Behavioral and brain measures evidence from a brain health perspective - Franco-O´Byrne, Daniel; Gonzalez-Gomez, Raul; Morales Sepúlveda, Juan Pablo; Vergara, Mayte; Ibañez, Agustin; Huepe, David (Frontiers in Psychology, 2023)
Early detection of depression is a cost-effective way to battle adverse outcomes on brain physiology, cognition, and health. We propose that loneliness and social adaptation are key factors that can anticipate depressive symptoms. Here we analyzed data from two separate samples to evaluate the associations between loneliness, social adaptation, depressive symptoms, and their neural correlates. For both samples, hierarchical regression models on self-report data showed that loneliness and social adaptation have negative and positive effects on depressive symptoms, respectively. Further, social adaptation reduces the effects of loneliness on depressive symptoms. Structural connectivity analysis revealed that depressive symptoms, loneliness, and social adaptation shared a common neural substrate. Functional connectivity analysis revealed that only social adaptation was associated with connectivity in parietal areas. Our results suggest that loneliness is a strong risk factor for depressive symptoms. Both variables are associated with alterations of white matter structures known to underlie emotion dysregulation and cognitive impairment. However, socio-adaptive skills may protect against the harmful effects of loneliness and depression. Structural and functional correlates of social adaptation could indicate a protective role through long and short-term effects, respectively. These findings may aid approaches to preserve brain health.